The Canada-United States trade in softwood lumber. - Lynch, Robert W. (University of Ottawa (Canada), 1997)
The thesis examines a long-standing North American trade dispute. At the centre of the conflict is the allegation by the U.S. softwood lumber industry that low provincial government stumpage fees constitute a subsidy to the Canadian softwood lumber industry. The thesis evaluates the subsidy allegation in the context of the British Columbia forest sector. The amount of Ricardin rent captured by the B.C. forest industry is decisive evidence leading to the conclusion that there is no provincial government subsidy to the softwood lumber industry. The argument is supported by evidence that lower stumpage fees in British Columbia only compensate for high costs in other areas of production. The outcome of the softwood lumber dispute is of critical importance to Canada.
Keywords: Economics, Agricultural.